LIBRARY DIGITALIZATION THROUGH THE PROVISION OF FACILITIES OF SEKOLAH INDONESIA KUALA LUMPUR (SIKL)’S LIBRARY - Sirojuzilam Hasyim; Irsad; M. Syafii; Sukardi (RADJA PUBLIKA, 2022)
The international community service initiative conducted at the Sekolah Indonesia Kuala Lumpur aims to provide real benefits in the effort to create a digital library at SIKL, which can enhance the learning interest of students at Sekolah Indonesia Kuala Lumpur, Malaysia and as a learning media that is easier to accessible and enjoyable, which will ultimately contribute to the development of quality human resources capable of competing in the future. The International service provided by the Postgraduate Lecturer of Economics, through the program “Library Digitalization Through the Provision of Library Facilities of Sekolah Indonesia Kuala Lumpur (SIKL)’s will support the facilities for a digital library at SIKL. Library facilities at SIKL are still limited. Given this situation, there is a need for a media that can facilitate the search for information and broaden knowledge to increase interest in learning for SIKL students. These facilities include PCs, TVs, and Speakers. The results of the community service are expected to contribute to enhancing interest in learning and facilitating the learning process at Sekolah Indonesia Kuala Lumpur, Malaysia.